1975
DOI: 10.1902/jop.1975.46.1.45
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Fluoride Exposure on Fluoride, Citrate and Carbonate Content of Human Cementum

Abstract: A study was conducted to determine the values of several chemical components of dental cementum. Extracted teeth from continuous residents of low, optimal, and high natural fluoride areas were selected to determine the effects of fluoride exposure and age on the fluoride, citrate and carbonate content of cervical and apical areas of sound and periodontally diseased human cementum. 1. For normal cementum the mean fluoride content of all 18 groups was 0.443 plus or minus 0.04%on an ash basis and 0.253 plus or mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…in some instances using pooled samples, the F concentrations reported presently cannot immediately be compared with the earlier data [Yoon et al, 1960a. b: Singer andArmstrong, 1962;Yardeni et al, 1963;Gedalia et al, 1965;Stepnick et al, 1975]. It can be stated, however, that the concentrations observed generally were within the range reported in the cementum of individuals living in low fluoride areas, with the exception that higher values, up to 0.6°/o by weight, were found close to the ce mentum surface.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…in some instances using pooled samples, the F concentrations reported presently cannot immediately be compared with the earlier data [Yoon et al, 1960a. b: Singer andArmstrong, 1962;Yardeni et al, 1963;Gedalia et al, 1965;Stepnick et al, 1975]. It can be stated, however, that the concentrations observed generally were within the range reported in the cementum of individuals living in low fluoride areas, with the exception that higher values, up to 0.6°/o by weight, were found close to the ce mentum surface.…”
Section: Discussionsupporting
confidence: 53%
“…Concentrations up to 0.9% of the ash weight have been reported, while some authors have found considerably lower values [Yoon et al, 1960a;Singer and Armstrong, 1962;Yardeni et al, 1963;Gedalia et al, 1965;Stepnick et al, 1975], There is a gen eral increment in fluoride content of normal cervical and apical cementum, both with age and fluoride exposure, and the mean fluoride content of cervical cementum is greater than that of apical cementum [Brudevold et al, 1960;Stepnick et al, 1975]. The ash content of cementum is 48-65% of the dry weight [Nakata et al, 1972].…”
mentioning
confidence: 99%
“…Mean P concentrations have been found to vary from 11.6 to 13.49% dry wt (68–71) or 16.6–20.0% ash (72). F concentrations in cementum are dependent on the level of systemic and local F exposure and show an increase with age (72–76), stronger F concentrations in the drinking water, and greater duration of exposure to the oral environment (72, 73, 77). In an optimally fluoridated area (0.8–1.3 ppm), concentrations at the cervical, middle and apical third of human cementum have been reported to range from 0.2 to 0.9% wt (72, 73, 77), 0.25–0.79% wt (73), and 0.15–0.8% wt (72, 73, 77), respectively.…”
Section: A Quantitative Analysis Of the Mineral Composition Of Human mentioning
confidence: 99%
“…6 In several studies, it has been shown that the concentration of fluoride in cementum is highest among the calcified tissues, [8][9][10] and the amount of accumulated fluoride in cementum increases by age. 11,12 It has been shown that fluoride stimulates the formation of new bone, primarily via an increase in osteoblast number in vitro 13 and in vivo. 14 It is also believed that sodium fluoride directly inhibits osteoclastic activity by preventing calcium ion release and directly suppresses osteoclast acidity.…”
Section: Introductionmentioning
confidence: 99%